Tuber-to-Anterior Process Angle (TAPA): A cadaveric study and surgical technique for placing axial calcaneal screws. Issue 7 (July 2019) - Stupay, Kristen L.; Briceño, Jorge; Velasco, Brian T.; Miller, Christopher P.; Kwon, John Y.
Highlights: We describe a simple technique that facilitates the placement of axial calcaneal screws. The Tuber-to-Anterior Process Angle (TAPA) describes the calcaneal long-axis as it relates to the long-axis of the foot. The TAPA is approximately 10 degrees laterally deviated from the long-axis of the foot. Knowledge of this angle simplifies placement of P:A screws in the calcaneus. Understanding this relationship reduces reliance on intraoperative axial fluoroscopy and increases operative efficiency. Abstract: We describe results of a cadaveric study and an accompanying surgical technique which simplifies posterior-to-anterior axial screw placement into the calcaneus, often utilized during fixation of displaced intra-articular calcaneus fractures or calcaneal osteotomies. By defining the Tuber-to-Anterior Process Angle (TAPA), this technique facilitates axial screw placement, thereby decreasing reliance on intraoperative fluoroscopy and reducing operative time.